Cybersecurity Challenges in Digital Health Infrastructures Toward a Secure E-Health Ecosystem - Coșa, Oana Ștefania; Golea, Daniela Georgiana; Radu, Andreea Florina (Technium Social Sciences Journal, 2025)
The accelerated digitalization of health systems globally has brought significant improvements in accessibility, interoperability, and clinical decision-making, yet it has simultaneously exposed critical vulnerabilities in digital health infrastructures that are increasingly targeted by sophisticated cyber threats which compromise patient safety, operational continuity, and data sovereignty; this article presents an interdisciplinary analysis of cybersecurity challenges affecting e-health ecosystems, combining perspectives from public health and security studies to assess institutional preparedness, map systemic vulnerabilities, and evaluate policy responses in light of recent cyberattacks on hospitals and digital platforms in Europe, Asia, and the United States, while introducing an original conceptual model aimed at securing digital health infrastructures through integrated governance, real-time threat coordination, and strategic resilience mechanisms that align cybersecurity with national health priorities and global security agendas.